2011
DOI: 10.1108/09556221111136520
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the tensile behaviour of needle punched nonwoven geotextiles

Abstract: Purpose -The purpose of this paper is to propose a theoretical model to predict the mechanical behaviour of needle punched heavy geotextiles in uniaxial tensile test. Design/methodology/approach -The model was constructed using theory of layered composite materials and finite element method. The properties of a reference fabric were used as initial data in theoretical calculations and a commercially available finite element program was chosen to carry out stress analysis. A comparison is made between theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The optimal experimental curves shown in Figure (b) consists two regions: a near linear increasing portion and the slowly developing phase. A linear elastic behavior in the first region was under a small load, and then the tensile strain–stress curves exhibited a slowly developing phase until break, which is similar with earlier results . The phenomenon could be explained by the two‐step breaking mechanism similar as nonwoven webs .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The optimal experimental curves shown in Figure (b) consists two regions: a near linear increasing portion and the slowly developing phase. A linear elastic behavior in the first region was under a small load, and then the tensile strain–stress curves exhibited a slowly developing phase until break, which is similar with earlier results . The phenomenon could be explained by the two‐step breaking mechanism similar as nonwoven webs .…”
Section: Resultssupporting
confidence: 88%
“…A linear elastic behavior in the first region was under a small load, and then the tensile strain–stress curves exhibited a slowly developing phase until break, which is similar with earlier results . The phenomenon could be explained by the two‐step breaking mechanism similar as nonwoven webs . When a small load is applied, the nanofibers in the webs structure tended to align and extend along the stretching direction, resulting in near linear elastic behavior.…”
Section: Resultssupporting
confidence: 87%
“…An analytical method was proposed to predict stiffness parameters of heavy nonwoven geotextiles using layer theory and uniaxial loading conditions. 21 The results of that study was compared with FEA and it was revealed similar stresses in identical fabrics. Later, the effects of manufacturing parameters on the tensile stiffnesses for thermally bonded nonwoven structures was studied by utilizing an efficient and novel numerical method based on finite element analysis.…”
Section: Tensile Behaviormentioning
confidence: 92%
“…The tensile behavior of non-woven fabrics was theoretically predicted by using orthotropic and non-linear finite elements. Comparison made between the theoretical calculations and experimental data with various stress values and strain distributions (Erdogan and Erdem, 2011).…”
Section: Introductionmentioning
confidence: 99%